Al2O3/Al hybrid nanolaminates with superior toughness, strength and ductility - Paul Baral; Sahar Jaddi; Hui Wang; Andrey Orekhov; Nicolas Gauquelin; Alireza Bagherpour; Frederik Van Loock; Michaël Coulombier; Audrey Favache; Morgan Rusinowicz; Johan Verbeeck; Stéphane Lucas; et al. (Nature Communications, 2025)
Abstract Amorphous alumina is hard but brittle like all ceramic type materials which affects durability under impact or scratch. Here we show that alumina layers below 100 nm thickness when stacked with aluminum interlayers exhibit exceptional performances including toughness equal to 300 J.m−2 determined by on chip nanomechanics. This is almost two orders of magnitude higher than bulk alumina and higher than any other thin hard coatings. In addition, a hardness above 8 GPa combines with a fracture strain above 5%. The origin of this superior set of properties is unravelled via in-situ TEM and mechanical models. The combination of constrained alumina layers with ductile behavior, strong “accommodating” interfaces, giant shear deformability of Al layers, and plasticity-controlled crack shielding cooperate to stabilize deformation, dissipate energy and arrest cracks. These performances unlock several options of applications of Al2O3 in which brittleness under contacts prevents benefiting from remarkable functional properties and chemical stability.